Odpowiedź :
Odpowiedź:
1. 1/3x-2 = x +2
1/3x-x = 2+2
-2/3x= 4 / :(-2/3)
x= 4*(-3/2 ) ( skracamy 4 i 2 przez 2)= 2*(-3)= - 6
x= - 6
spr.. 1/3 *(-6) -2 = - 6 +2 ( skracamy 3 i 6 przez 3)
-2 -2= -4
-4= - 4
L=P
2. 1- 6/7 x = 4/7
-6/7 x= 4/7 -1
-6/7 x= - 3/7 /:6/7
x= -3/7 *(-7/6) ( skracamy 7 i 7 przez 7, oraz 3 i 6 przez 3)
x= 1/2
spr... 1- 6/7 *1/2 = 4/7 ( skracamy 6 i 2 przez 2)= 4/7
1- 3/7= 4/7
4/7=4/7
L=P
3. 6( 1/4 x -2)= 18
6/4x -12= 18
6/4x= 18+12
6/4x= 30 /: 6/4
x= 30 *4/6 ( skracamy 30 i 6 przez 6)
x= 5*4= 20
x=20
spr... 6/4 *20 -12= 18 ( skracamy 20 i 4 przez 4)
6*5- 12= 18
30-12= 18
18=18
L=P
Szczegółowe wyjaśnienie:
1.
[tex]\frac{1}{3}x -2 = x+2 \ \ \ |\cdot3\\\\x-6=3x+6\\\\x-3x = 6+6\\\\-2x = 12 \ \ \ |:(-2)\\\\\boxed{x = -6}[/tex]
2.
[tex]1 - \frac{6}{7}x = \frac{4}{7} \ \ \ |\cdot7\\\\7-6x= 4\\\\-6x = 4-7\\\\-6x = -3 \ \ \ |:(-6)\\\\\boxed{x = \frac{1}{2}}[/tex]
3.
[tex]6(\frac{1}{4}x - 2) = 18 \ \ \ |:6\\\\\frac{1}{4}x-2 = 3\\\\\frac{1}{4}x = 3+2\\\\\frac{1}{4}x = 5 \ \ \ |\cdot4\\\\\boxed{x = 20}[/tex]